Engagement Strategies in the USU English Debate Forum: An Appraisal Theory Perspective - Faninsky Aryanti La Ajina Hasibuan; Deliana Deliana; Nurlela Nurlela; Rusdi Noor Rosa (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2025)
Previous studies on engagement have a primary focus on textual discourse or written communication analysis rather than on interactive, spoken communication. This leaves a room for further exploration into how engagement functions dynamically, such as in debates. This study aims to find out the engagement strategies used in the USU English Debate Forum 2023 through the lens of Martin and White’s (2005) appraisal theory of engagement. Using a qualitative content analysis, this study categorizes debate discourse into monoglossic and heteroglossic engagement systems to analyze how the debaters construct meaning, position themselves in relation to their audience, and employ linguistic features to sustain engagement. The data were collected using observation and documentation methods and were analyzed using an interactive model of data analysis. The findings indicate that heteroglossic engagement overwhelmingly dominates the debate discourse, accounting for 83.3% of the engagement strategies used. Among the heteroglossic features, dialogic contraction strategies such as Deny (21.17%) and Counter (16.47%) were frequently employed, highlighting the competitive nature of debate discourse. Dialogic expansion, particularly Entertainment (32.94%), also played a significant role, allowing the debaters to introduce assessments of probability and possibility. The results suggest that the debaters strategically navigate linguistic resources to challenge opposing arguments, reinforce their stance, and engage with alternative perspectives. This study contributes to the understanding of engagement strategies in academic debates, offering implications for debate training and rhetorical education.